Measuring Success in Health Care Value-Based Purchasing Programs Findings from an Environmental Scan, Literature Review, and Expert Panel Discussions - Damberg, Cheryl L. (RAND Corporation, 2014)
Value-based purchasing (VBP) refers to a broad set of performance-based payment strategies that link financial incentives to health care providers' performance on a set of defined measures in an effort to achieve better value. This report summarizes the current state of knowledge about VBP, drawing on a review of the published literature and other documents about VBP programs and discussions with a panel of experts on VBP.